New host records and a checklist of fishes infected with Austrodiplostomum compactum (Digenea: Diplostomidae) in Brazil - Ramos, Igor Paiva [UNESP]; Franceschini, Lidiane [UNESP]; Zago, Aline Cristina [UNESP]; Zica, Érica De Oliveira Penha [UNESP]; Wunderlich, Alison Carlos [UNESP]; Carvalho, Edmir Daniel [UNESP]; Silva, Reinaldo José Da [UNESP] (Colégio Brasileiro de Parasitologia Veterinária, 2013)
This study reports the infection of fishes by Austrodiplostomum compactum metacercariae in the Chavantes reservoir, medium Paranapanema River, municipality of Ipaussu, São Paulo State, Brazil. Twenty-three fish species were analysed, and 13 were infected with A. compactum metacercariae (56.5%) in their eyes. The following six fish species are new hosts for this metacercaria: Crenicichla haroldoi (1/1), Eigenmannia trilineata (11/6), Hoplosternum littorale (11/1), Iheringichthys labrosus (17/2), Leporinus amblyrhynchus (11/1), and Piaractus mesopotamicus (3/1). These new species increase the number of Brazilian fish species infected with this parasite to 36. Based on these findings, we hypothesise that the metacercariae larval stage of the parasite has a low specificity for the second intermediate host (fish). The majority of fish species infected in Brazil belong to the Loricariidae and Cichlidae families. For the fish species with higher mean abundances in Brazil, six are non-native species, and currently, Plagioscion squamosissimus has the highest mean abundance. The majority of fish species infected with A. compactum in Brazil are concentrated in the Paraná basin, although this may be related to the distribution of researchers.

Este estudo relata a infecção por metacercárias de Austrodiplostomum compactum em peixes do reservatório de Chavantes, médio Paranapanema, Ipaussu, São Paulo, Brasil. Vinte e três espécies de peixes foram analisadas, e 13 estavam infectadas com metacercárias (56,5%) em seus olhos. Seis espécies de peixes foram registradas como novos hospedeiros: Crenicichla haroldoi (1/1), Eigenmannia trilineata (11/6), Hoplosternum littorale (11/1), Iheringichthys labrosus (17/2), Leporinus amblyrhynchus (11/1), and Piaractus mesopotamicus (3/1), aumentando para 36 o número de peixes brasileiros infectados por este parasita. Assim, inferimos que este estágio larval do parasita possui baixa especificidade parasitária em relação ao seu segundo hospedeiro intermediário (peixes). No Brasil, a maioria das espécies de peixes infectadas pertence às famílias Loricariidae e Cichlidae. Quanto às espécies de peixes com as maiores abundâncias médias no Brasil, seis são espécies não-nativas, sendo Plagioscion squamosissimus a espécie com a maior abundância média. Ainda, a maioria das espécies de peixes infectadas por A. compactum no Brasil, estão concentradas na bacia do Paraná, sendo este fato possivelmente relacionado com a distribuição de pesquisadores.
Novos registros de hospedeiros e “checklist” de peixes infectados por Austrodiplostomum compactum (Digenea: Diplostomidae) no Brasil
Keywords: Freshwater fishes; parasite; Trematoda; metacercariae; infection; Paraná basin; Peixes de água doce; parasita; Trematoda; metacercária; infecção; bacia do Paraná